Applying lessons from human papillomavirus vaccines to the development of vaccines against Chlamydia trachomatis. (2nd November 2018) - Frietze, Kathryn M.; Lijek, Rebeccah; Chackerian, Bryce
ABSTRACT: Introduction : Chlamydia trachomatis ( Ct ), the most common bacterial sexually transmitted infection (STI), leads to pelvic inflammatory disease, infertility, and ectopic pregnancy in women. In this Perspective, we discuss the successful human papillomavirus (HPV) vaccine as a case study to inform Ct vaccine efforts. Areas covered : The immunological basis of HPV vaccine-elicited protection is high-titer, long-lasting antibody responses in the genital tract which provides sterilizing immunity. These antibodies are elicited through parenteral administration of a subunit vaccine based on virus-like particles (VLPs) of HPV. We present three lessons learned from the successful HPV vaccine efforts: (1) antibodies alone can be sufficient to provide protection from STIs in the genital tract, (2) the successful generation of high antibody levels is due to the multivalent structure of HPV VLPs, (3) major challenges exist in designing vaccines that elicit appropriate effector T cells in the genital tract. We then discuss the possibility of antibody-based immunity for Ct . Expert commentary : In this Perspective, we present a case for developing antibody-eliciting vaccines, similar to the HPV vaccine, for Ct . Basic research into the mechanisms of Ct entry into host cells will reveal new vaccine targets, which may be antigens against which antibodies are not normally elicited during natural infection.